Cat owners’ perceptions toward flea infestation and flea-borne diseases: impact for public health and community awareness - Wahid, Noor Azrizal; Azirun, Mohd Sofian; Low, Van Lun; Chen, Chee Dhang; Shohaimi, Shamarina (Taylor and Francis, 2021)
A structured questionnaire was distributed to a total of 531 cat owners in Peninsular Malaysia to evaluate their perceptions toward fleas and flea-borne diseases (FBD) using a knowledge-attitude-practice (KAP) approach. This study showed that majority of cat owners (50.5%) had a moderate level of knowledge on fleas, while 65.3% of them had a relatively low level of knowledge on FBD. However, most of them had positive attitudes (87.9%) and good practices (94.5%) toward efforts on prevention from flea infestation and FBD. Statistical analysis showed significant associations between knowledge on fleas and FBD toward demographic and pet ownership profiles of the respondents. Educated cat owners from urban area were more likely to have positive attitudes toward prevention of fleas and FBD. Female cat owners with monthly income of RM 5,001–7,000 ($1143–1600) were more likely to have good practices. Middle-aged cat owners showed the highest odds toward both positive attitudes and good practices. Correlation analyses indicated significant linear relationships between both knowledge, which were also associated with attitudes, but not with practices.